Bacteriostatic deodorizing cat litter and preparation method thereof
Patent Information
- Application Number
- CN202511251664.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-03
AI Technical Summary
[0003]目前市面上的猫砂按其基质材料主要可分为以下几类:(1) 矿物猫砂,主要以膨润土、沸石为代表,凭借其优异的吸水性和结团性占据市场主导地位,但其粉尘较大,且自身不具备抗菌功能,仅依靠物理吸附掩盖异味,易成为细菌滋生的温床,需频繁更换,如申请号为CN201811315803 .0的发明专利,其以负载银离子的硅藻土、除味硅藻土和羧甲基淀粉钠改性钙基膨润土制作猫砂,具有结团、除臭、抗菌抑菌且利用低品位的矿物质,但其粉尘率较高,且难以控制异味问题;(2) 植物纤维猫砂,以豆腐渣、玉米芯、木屑等为原料,具有环保可降解、粉尘少的优点,但植物基质本身富含有机物,在潮湿环境下极易霉变和滋生细菌,对宠物健康构成潜在威胁;(3) 硅胶猫砂,主要成分为二氧化硅,吸湿性强、粉尘极少,但其除臭主要依赖物理吸附,饱和后除臭效果骤减,且无法抑制细菌繁殖
1)本发明同时使用十六烷基氯化铵、椰油酸单乙醇酰胺对膨润土进行协同改性时,能够使猫砂表现出更优的吸液性、抗结团性、抗菌性、除臭性和粉尘性,尤其是在抗菌性、除臭性方面。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of pet products, specifically relating to an antibacterial and deodorizing cat litter and its preparation method. Background Technology
[0002] With social development and improved living standards, pet ownership has become an important part of many families. Cat litter, as an essential item for cat owners, directly impacts the hygiene of the home environment and the user experience. Ideal cat litter should possess excellent absorbency, clumping ability, low dust content, and effectively control bacterial growth and odor problems caused by feces and urine.
[0003] Currently, cat litter on the market can be mainly divided into the following categories according to its matrix material: (1) Mineral cat litter, mainly represented by bentonite and zeolite, dominates the market due to its excellent water absorption and clumping properties, but it has a large amount of dust and does not have antibacterial function. It only relies on physical adsorption to cover up odors, which can easily become a breeding ground for bacteria and needs to be replaced frequently. For example, the invention patent with application number CN201811315803.0 uses diatomaceous earth loaded with silver ions, deodorizing diatomaceous earth and sodium carboxymethyl starch modified calcium-based bentonite to make cat litter. It has clumping, deodorizing, antibacterial and bacteriostatic properties and uses low-grade minerals, but its dust rate is high and it is difficult to control the odor problem; (2) Plant fiber cat litter, made from tofu residue, corn cob, wood chips and other raw materials, has the advantages of being environmentally friendly and biodegradable and having less dust, but the plant matrix itself is rich in organic matter, which is very easy to mold and breed bacteria in a humid environment, posing a potential threat to the health of pets; (3) Silica gel cat litter is mainly composed of silica. It has strong moisture absorption and very little dust, but its deodorization mainly relies on physical adsorption. Once saturated, its deodorization effect drops sharply, and it cannot inhibit bacterial growth.
[0004] To overcome the aforementioned shortcomings, many improvements have emerged in the existing technology aimed at enhancing the antibacterial and deodorizing functions of cat litter. These improvements are primarily achieved by adding functional additives to the cat litter matrix. Summary of the Invention
[0005] To overcome the problems existing in the prior art, the present invention aims to provide an antibacterial and deodorizing cat litter and its preparation method. Bentonite is synergistically modified with hexadecyl ammonium chloride and cocoyl monoethanolamide to form a polyacrylic acid gel resin layer on the surface of the modified bentonite. The polyacrylic acid gel resin layer has an IPN three-dimensional network porous structure, which can improve the cat litter's liquid absorption, anti-caking, antibacterial, deodorizing and lower dust content.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: An antibacterial and deodorizing cat litter, characterized in that it comprises 40-80 parts by weight of modified bentonite, 8-24 parts by weight of chitosan, 15-40 parts by weight of sodium acrylate, 1-7 parts by weight of styrene, 5-12 parts by weight of maleic anhydride, 2-8 parts by weight of methacrylic acid, 1-5 parts by weight of crosslinking agent, 0.1-1 parts by weight of initiator, and 30-100 parts by weight of deionized water.
[0007] Preferably, the modified bentonite is prepared by dispersing a surfactant and bentonite in water, stirring to form a suspension, continuing to stir and heating to 30-50°C, reacting for 1-2 hours, filtering and drying to obtain the modified bentonite.
[0008] Preferably, the surfactant comprises cocoyl monoethanolamide and hexadecyl ammonium chloride.
[0009] Preferably, the mass ratio of the cocoyl monoethanolamide to hexadecyl ammonium chloride is 1:2-5.
[0010] Preferably, the bentonite has a particle size of 1-10 mm.
[0011] Preferably, the mass ratio of the surfactant to bentonite is 1:10-40.
[0012] Preferably, the acid anhydride is one or more of maleic anhydride, itaconic anhydride, fumarate monoester, and itaconic acid monoester.
[0013] Preferably, the acid anhydride is maleic anhydride.
[0014] Preferably, the crosslinking agent includes one or more of pentaerythritol triacrylate, trimethylolpropane triacrylate, dipropylene glycol diacrylate, and N,N'-methylenebisacrylamide.
[0015] Preferably, the initiator is one or more of APS, KPS, BPO, AIBN, AIVN, and redox initiators.
[0016] A method for preparing antibacterial and deodorizing cat litter, characterized by comprising the following steps: Step 1: Weigh the raw materials; Step 2: Mix chitosan, sodium acrylate, styrene, maleic anhydride, methacrylic acid, crosslinking agent, initiator and deionized water, and stir until uniformly dispersed to form an emulsion; Step 2: Place the modified bentonite into the emulsion from Step 2, stir thoroughly, soak for 2-5 hours, dry and react at 25-85℃ for 20-60 minutes, cool down, put the mixture into a granulator for granulation, then put the formed granules into an oven for drying, sieve, and discharge to obtain antibacterial and deodorizing cat litter.
[0017] Preferably, the diameter of the granulated particles is between 1 mm and 8 mm.
[0018] Preferably, the oven temperature is 150-300℃ and the drying time is 1-3 hours.
[0019] The beneficial effects of this invention are as follows: 1) When the present invention uses hexadecyl ammonium chloride and cocoyl monoethanolamide to synergistically modify bentonite, the cat litter can exhibit better liquid absorption, anti-caking, antibacterial, deodorizing and dust-free properties, especially in terms of antibacterial and deodorizing properties.
[0020] 2) This invention involves soaking and adsorbing chitosan and polymerizable monomer solutions onto the surface of modified bentonite, followed by in-situ polymerization to form a polyacrylic acid gel resin layer on the surface of the modified bentonite. This polyacrylic acid gel resin layer is formed by polymerizing sodium acrylate monomers, maleic anhydride monomers, styrene monomers, and crosslinking agents in the presence of chitosan molecular chains. This process creates a microscopic IPN three-dimensional network porous structure. The resin layer coating the surface of the modified bentonite provides elasticity and further increases porosity. The carboxyl groups in the polyacrylic acid gel resin layer can chelate odor substances such as ammonia and organic amines. After absorbing urine, the polyacrylic acid gel resin layer on the surface of the modified bentonite swells due to liquid absorption, and the pore size in the microscopic three-dimensional network structure becomes smaller. Therefore, it can adsorb and lock urine and odor substances within the polyacrylic acid gel resin layer, thereby improving the liquid absorbency, anti-caking properties, antibacterial properties, deodorizing properties, and reducing dust in cat litter. Detailed Implementation
[0021] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The present invention will be further explained and described below with reference to specific embodiments.
[0022] Preparation Example 1 The preparation method of modified bentonite is as follows: The modified bentonite is prepared by dispersing hexadecyl ammonium chloride, cocoyl monoethanolamide, and bentonite in water, stirring to form a suspension, continuing stirring and heating to 30°C, reacting for 1 hour, filtering, and drying to obtain the modified bentonite. The particle size of the bentonite is 2 mm. The mass ratio of the surfactant to bentonite is 1:20. The mass ratio of cocoyl monoethanolamide to hexadecyl ammonium chloride is 1:2.
[0023] Preparation Example 2 The preparation method of modified bentonite is as follows: The modified bentonite is prepared by dispersing hexadecyl ammonium chloride and bentonite in water, stirring to form a suspension, continuing stirring and heating to 30°C, reacting for 1 hour, filtering, and drying to obtain the modified bentonite. The particle size of the bentonite is 2 mm. The mass ratio of the surfactant to bentonite is 1:20.
[0024] Preparation Example 3 The preparation method of modified bentonite is as follows: The modified bentonite is prepared by dispersing cocoyl monoethanolamide and bentonite in water, stirring to form a suspension, continuing stirring and heating to 30°C, reacting for 1 hour, filtering, and drying to obtain the modified bentonite. The particle size of the bentonite is 2 mm. The mass ratio of the surfactant to bentonite is 1:20.
[0025] Example 1 The raw materials for the antibacterial and deodorizing cat litter include 53 parts by weight of modified bentonite prepared in Preparation Example 1, 10 parts by weight of chitosan, 20 parts by weight of sodium acrylate, 3 parts by weight of styrene, 8 parts by weight of maleic anhydride, 4 parts by weight of methacrylic acid, 1 part by weight of crosslinking agent N,N'-methylenebisacrylamide, 0.5 parts by weight of initiator KPS, and 40 parts by weight of deionized water.
[0026] Methods for preparing antibacterial and deodorizing cat litter include: Step 1: Mix chitosan, sodium acrylate, styrene, maleic anhydride, methacrylic acid, crosslinking agent, initiator and deionized water, and stir until uniformly dispersed to form an emulsion; Step 2: Place the modified bentonite prepared in Example 1 into the emulsion from Step 1, stir thoroughly, soak for 2.5 hours, dry at 45°C for 30 minutes, cool down, and put the mixture into a granulator, controlling the particle diameter to be 3mm-5mm. Next, place the formed granules in a 200°C oven to dry for 1.5 hours, sieve, and discharge to obtain antibacterial and deodorizing cat litter.
[0027] Comparative Example 1 An antibacterial and deodorizing cat litter was prepared according to the method of Example 1, the only difference being that chitosan was replaced with sodium acrylate.
[0028] Comparative Example 2 An antibacterial and deodorizing cat litter was prepared according to the method of Example 1, the only difference being that maleic anhydride was replaced with sodium acrylate.
[0029] Example 2 An antibacterial and deodorizing cat litter was prepared according to the method of Example 1, the only difference being that the modified bentonite prepared in Example 1 was replaced with the modified bentonite prepared in Example 2.
[0030] Example 3 An antibacterial and deodorant cat litter, which is prepared according to the method of Example 1, with the only difference that the modified bentonite prepared in Preparation Example 1 is replaced with the modified bentonite prepared in Preparation Example 3.
[0031] Performance test Using physiological saline containing 1g / 100mL urea as the absorption object to simulate cat urine, the surface of the cat litter prepared in each of Examples 1-3 and Comparative Examples 1-2 is sprayed respectively. The liquid absorbency, clumping property, antibacterial property, deodorization property and dust property of the cat litter after absorbing the simulated cat urine are evaluated, and the results are shown in the following table: Liquid absorbency: 50mL of physiological saline containing 1g / 100mL urea is sprayed on the surface of 1000g of the cat litter prepared in each of Examples 1-3 and Comparative Examples 1-2 respectively, and the time required for the cat litter to completely absorb the liquid is tested to evaluate the liquid absorbency.
[0032] Clumping property: Spread the cat litter flat in a container; add 10mL of physiological saline containing 1g / 100mL urea to the cat litter from a height of 2.5cm within 4 to 5 seconds; after 10 seconds, pour out the clump test block, observe and record the shape of the clump. Let the test block fall freely from a height of 75cm, record whether the test block is broken or not, and the test block that does not break is qualified.
[0033] Antibacterial property: The antibacterial property test is carried out according to the standard GB / T21551.2-2010.
[0034] Deodorization property: Pour 20g of cat litter into a conical flask, use a pipette to take 0.1ml of 100ppm ammonia aqueous solution, drop it onto the surface of the cat litter in the conical flask, cover with a rubber stopper and seal the opening of the rubber stopper with adhesive tape. After 30 minutes, cut off the end seals of the ammonia gas detection tube, insert the tail end of the detection tube into the air inlet of the vacuum sampler, and insert the other end into the conical flask with the rubber stopper. Pull the sampler handle to the 100ml gear position, and when the indicator in the detection tube stops changing color, read the scale reached by the yellow column. The value obtained by subtracting the reading of the ammonia gas detection tube from 100ppm is the ammonia absorption capacity.
[0035] Dust property: Weigh 200g of cat litter particle sample, put it into a small ball mill, and cover the porcelain lid tightly. Place it on the ball mill, start the machine to run for 20 minutes, take out the sample and sieve it through a 1mm sieve, weigh the weight of the dust under the sieve, and the ratio of the weight of the dust under the sieve to 200g is the pulverization rate of the product.
[0036] Table 1 Properties of the antibacterial and deodorant cat litter
[0037] As can be seen from the comparison of Example 1, Comparative Example 1, and Comparative Example 2, the cat litter prepared in Example 1 of the present invention has a shorter liquid absorption time, higher antibacterial properties, higher ammonia absorption, and lower pulverization rate, that is, it exhibits better liquid absorption, anti-caking properties, antibacterial properties, deodorization, and dust resistance. This is likely because, in Embodiment 1 of the present invention, a solution of chitosan and polymerizable monomers is soaked and adsorbed on the surface of modified bentonite, followed by in-situ polymerization to form a polyacrylic acid gel resin layer on the surface of the modified bentonite. This polyacrylic acid gel resin layer is formed by polymerization of sodium acrylate monomers, maleic anhydride monomers, styrene monomers, and crosslinking agents in the presence of chitosan molecular chains. This can form an IPN three-dimensional network porous structure at the microscopic level. The resin layer coating the surface of the modified bentonite provides elasticity and further increases porosity. Moreover, the carboxyl groups in the polyacrylic acid gel resin layer can chelate odor substances such as ammonia and organic amines. After absorbing urine, the polyacrylic acid gel resin layer on the surface of the modified bentonite swells due to liquid absorption, and the pore size in the microscopic three-dimensional network structure becomes smaller. Therefore, it can adsorb and lock urine and odor substances within the polyacrylic acid gel resin layer, thereby improving the liquid absorbency, anti-caking properties, antibacterial properties, deodorizing properties, and reducing dust in cat litter. Comparative Example 1 did not use chitosan; instead, in-situ polymerization of sodium acrylate monomers, maleic anhydride monomers, styrene monomers, and a crosslinking agent was performed directly on the surface of modified bentonite. The resulting three-dimensional network porous structure was not as dense as the IPN three-dimensional network porous structure of Example 1. Furthermore, chitosan itself has antibacterial properties; omitting this component would lead to a decrease in its liquid absorption, anti-caking properties, antibacterial properties, deodorization, and dust-generating properties. Comparative Example 2 replaced maleic anhydride with sodium acrylate, and replaced the multi-carboxyl maleic anhydride with monocarboxyl sodium acrylate. This reduced the carboxyl group content on the polyacrylic acid gel resin chain, decreasing the number of carboxyl groups that could participate in liquid absorption, swelling, and chelation. Omitting this component would also lead to a decrease in its liquid absorption, antibacterial properties, deodorization, and dust-generating properties.
[0038] A comparison of Examples 1, 2, and 3 shows that the cat litter prepared in Example 1 of this invention has a shorter liquid absorption time, higher antibacterial properties, higher ammonia absorption, and lower pulverization rate, exhibiting superior liquid absorption, anti-caking properties, antibacterial properties, deodorization, and dust control. This is likely because the modified bentonite in Example 1 of this invention is synergistically modified with hexadecyl ammonium chloride and cocoyl monoethanolamide. Hexadecyl ammonium chloride has antibacterial properties and can perform intercalation modification of bentonite through cation exchange, achieving adsorption of odor substances through cation exchange. Cocoyl monoethanolamide has excellent solubilizing properties for odor substances and has amide groups, which can synergistically work with hexadecyl ammonium chloride to improve the adsorption of odor substances. Therefore, when hexadecyl ammonium chloride and cocoyl monoethanolamide are used simultaneously for synergistic modification of bentonite, superior liquid absorption, anti-caking properties, antibacterial properties, deodorization, and dust control are exhibited, especially in terms of antibacterial and deodorization properties.
[0039] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. An antibacterial and deodorizing cat litter, characterized in that, The modified bentonite comprises 40-80 parts by weight of modified bentonite, 8-24 parts by weight of chitosan, 15-40 parts by weight of sodium acrylate, 1-7 parts by weight of styrene, 5-12 parts by weight of acid anhydride, 2-8 parts by weight of methacrylic acid, 1-5 parts by weight of crosslinking agent, 0.1-1 parts by weight of initiator, and 30-100 parts by weight of deionized water. The modified bentonite is prepared by dispersing the surfactants cocoyl oleate monoethanolamide and hexadecyl ammonium chloride with bentonite in water, stirring to form a suspension, continuing stirring and heating to 30-50°C, reacting for 1-2 hours, filtering, and drying to obtain the modified bentonite. Chitosan and polymerizable monomer solutions are then impregnated and adsorbed onto the surface of the modified bentonite. Subsequently, through in-situ polymerization, a polyacrylic acid gel resin layer is formed on the surface of the modified bentonite. This polyacrylic acid gel resin layer is formed by the polymerization of sodium acrylate monomers, acid anhydride monomers, styrene monomers, and crosslinking agent in the presence of chitosan molecular chains, and can form an IPN three-dimensional network porous structure at the microscopic level.
2. The antibacterial and deodorizing cat litter according to claim 1, characterized in that: The mass ratio of the surfactant to bentonite is 1:10-40.
3. The antibacterial and deodorizing cat litter according to claim 1, characterized in that: The mass ratio of the coconut oil monoethanolamide to hexadecyl ammonium chloride is 1:2-5.
4. The antibacterial and deodorizing cat litter according to claim 1, characterized in that: The bentonite has a particle size of 1-10 mm.
5. The antibacterial and deodorizing cat litter according to claim 1, characterized in that: The acid anhydride is one or more of maleic anhydride, itaconic anhydride, fumarate monoester, and itaconic acid monoester.
6. The antibacterial and deodorizing cat litter according to claim 1, characterized in that: The acid anhydride is maleic anhydride.
7. The method for preparing antibacterial and deodorizing cat litter according to any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Weigh the raw materials; Step 2: Mix chitosan, sodium acrylate, styrene, acid anhydride, methacrylic acid, crosslinking agent, initiator and deionized water, and stir until uniformly dispersed to form an emulsion; Step 3: Place the modified bentonite into the emulsion from Step 2, stir thoroughly, soak for 2-5 hours, dry and react at 25-85℃ for 20-60 minutes, cool down, put the mixture into a granulator for granulation, then put the formed granules into an oven for drying, sieve, and discharge to obtain antibacterial and deodorizing cat litter.
8. The method for preparing antibacterial and deodorizing cat litter according to claim 7, characterized in that: The oven temperature is 150-300℃, and the drying time is 1-3 hours.
9. The method for preparing antibacterial and deodorizing cat litter according to claim 7, characterized in that: The granulated particles have a diameter of 1mm-8mm.
Citation Information
Patent Citations
Diatomite-based caking, deodorizing, antibacterial and bacteriostatic cat litter capable of being washed away by closestool and preparation method of cat litter
CN111149710A
Bacteriostatic and deodorant cat litter and preparation method thereof
CN115530081A
Bentonite cat litter enhancing, dust falling and deodorizing agent and application thereof
CN119790998A
